PENGARUH LIKUIDITAS, SOLVABILITAS, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2017 - Desinta Hermi Nugraheni, 15.05.52.0283; Irsad, Moch (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and determine the effect of liquidity, solvency, sales growth and firm size on profitability (ROA) in manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017.The sampling method used was purposive sampling, with a number of data processed as many as 201 companies. The analysis tool used is multiple regression analysis. The test hypothesis is used t-statistics and at a significant level of 0.05 or 5%.The results of this study show that liquidity and firm size have a significant positive effect on company profitability (ROA), solvency has a significant negative effect on company profitability (ROA), while sales growth has no effect on company profitability (ROA).